2005
DOI: 10.1128/mcb.25.10.4311-4320.2005
|View full text |Cite
|
Sign up to set email alerts
|

Misregulation of 2μm Circle Copy Number in a SUMO Pathway Mutant

Abstract: Attachment of the ubiquitin-like protein SUMO to other proteins is an essential process in Saccharomyces cerevisiae. However, yeast mutants lacking the SUMO ligases Siz1 and Siz2/Nfi1 are viable, even though they show dramatically reduced levels of SUMO conjugation. This siz1⌬ siz2⌬ double mutant is cold sensitive and has an unusual phenotype in that it forms irregularly shaped colonies that contain sectors of wild-typeappearing cells as well as sectors of enlarged cells that are arrested in G 2 /M. We have fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(118 citation statements)
references
References 47 publications
5
113
0
Order By: Relevance
“…The nibbled colony morphology of slx5Δ and slx8Δ mutants is reminiscent of that seen in SUMO mutants where it is known to be caused by overreplication of the 2μ circle plasmid (2μ) [24][25][26][27]. To determine whether 2μ was responsible for this phenotype in slx5Δ and slx8Δ mutants, we cured the cells of the plasmid by expressing a step-arrest mutant of the Flp recombinase [33].…”
Section: Sumoylation Defects In Slx5δ and Slx8δ Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nibbled colony morphology of slx5Δ and slx8Δ mutants is reminiscent of that seen in SUMO mutants where it is known to be caused by overreplication of the 2μ circle plasmid (2μ) [24][25][26][27]. To determine whether 2μ was responsible for this phenotype in slx5Δ and slx8Δ mutants, we cured the cells of the plasmid by expressing a step-arrest mutant of the Flp recombinase [33].…”
Section: Sumoylation Defects In Slx5δ and Slx8δ Mutantsmentioning
confidence: 99%
“…Rather than being perfectly circular, these colonies have uneven edges due to an unstable population of enlarged slow-growing cells that exhibit clonal lethality [7,24]. The phenotypes of these cells are exacerbated at low temperature and include a delay in the G2/M phase of the cell cycle [22,23,25]. It has recently been shown that the nibbled phenotype of sumoylation mutants occurs due to over-replication of the 2μ circle which is normally an innocuous plasmid found in most laboratory strains of Saccharomyces [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…All tagged MCM strains and the indicated mutations were integrated into the chromosomal locus of the gene of interest (supplemental Table 1) using standard yeast genetic methods unless otherwise noted. The yeast strains used here also have their 2-m circles removed, according to a previous study (24). Fluctuation analysis of GCRs was performed as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
“…The natural substrates of Slx5⅐Slx8-dependent ubiquitylation are unknown. The siz1⌬ siz2⌬ double mutant, slx5⌬, slx8⌬, ulp1, and certain NPC mutants accumulate as much as 10-fold higher than wt levels of 2 m DNA (Zhao et al, 2004;Chen et al, 2005;Dobson et al, 2005;Burgess et al, 2007;Ii et al, 2007b). A potential mechanism for SUMO's role in 2 m stability is suggested by the fact that Flp recombinase is modified by SUMO at a fairly high level (ϳ10%; Chen et al, 2005).…”
mentioning
confidence: 99%